Relatório de estágio técnico profissional em medicina veterinária: clínica médica de pequenos animais - Helden, Fernanda Lucas Von (2023)
The Professional Technical Internship (ETP) is extremely important in the training of Professional Veterinary Doctor. Through it, the academic can improve and put into practice the theoretical knowledge acquired during the undergraduate period. This work aims to describe all the activities carried out during the mandatory curricular internship in Veterinary Medicine at the Veterinary Hospital of Passo Fundo (HV-UPF), in the Small Animal Medical Clinic area. The internship was carried out from August 1st to October 23rd, 2023, comprising 432 hours, under local supervision by Veterinary Doctor Camila Marques Linck and guidance academic of Veterinary Doctor Profa. Dr. Heloísa Helena de Alcantara Barcellos. This report will cover the description of the internship location, infrastructure, team, monitored case series and activities developed. In addition to describing a case report of a feline, female, mixed breed, four years old, diagnosed with Feline Gingivitis-Stomatitis-Pharyngitis Complex.